2006
DOI: 10.4049/jimmunol.176.12.7438
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Independent, TLR-Induced IL-12p70 Production in Primary Human Monocytes

Abstract: IL-12p70 is a key cytokine for the induction of Th1 immune responses. IL-12p70 production in myeloid cells is thought to be strictly controlled by T cell help. In this work we demonstrate that primary human monocytes can produce IL-12p70 in the absence of T cell help. We show that human monocytes express TLR4 and TLR8 but lack TLR3 and TLR7 even after preincubation with type I IFN. Simultaneous stimulation of TLR4 and TLR8 induced IL-12p70 in primary human monocytes. IL-12p70 production in peripheral blood mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
94
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 55 publications
7
94
0
1
Order By: Relevance
“…However, in our study we used macrophages, a cell type that is different from endothelial cells, which can explain the discrepancy. In cooperation with TLR4 signaling, TLR7/8 was shown recently to induce IL-12p70 synthesis in human monocytes, triggering a potent Th1 response before T cell help is established (51). However, consistent with our results that TLR2 had little effect on the early induction of IFN-␤, a potential IL-12p70 inducer (20), the combination of TLR2 and TLR7/8 signaling was found unable to induce IL-12p70 in human monocytes (51).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, in our study we used macrophages, a cell type that is different from endothelial cells, which can explain the discrepancy. In cooperation with TLR4 signaling, TLR7/8 was shown recently to induce IL-12p70 synthesis in human monocytes, triggering a potent Th1 response before T cell help is established (51). However, consistent with our results that TLR2 had little effect on the early induction of IFN-␤, a potential IL-12p70 inducer (20), the combination of TLR2 and TLR7/8 signaling was found unable to induce IL-12p70 in human monocytes (51).…”
Section: Discussionsupporting
confidence: 67%
“…In cooperation with TLR4 signaling, TLR7/8 was shown recently to induce IL-12p70 synthesis in human monocytes, triggering a potent Th1 response before T cell help is established (51). However, consistent with our results that TLR2 had little effect on the early induction of IFN-␤, a potential IL-12p70 inducer (20), the combination of TLR2 and TLR7/8 signaling was found unable to induce IL-12p70 in human monocytes (51). Interestingly, we observed that TLR7 was essential for the early induction of IFN-␤ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we identified monocytes as the major source of IL-12p70 upon ssRNA stimulation within PBMC. The exclusive expression of TLR8 in monocytes (24,30), sensitivity toward inhibition by chloroquine, and siRNAmediated knock-down experiments support the concept of TLR8-dependent recognition of RNA-pLa complexes to be responsible for massive IL-12p70 induction. This previously unappreciated capability of monocytes to produce large amounts of IFN-␣ and IL12p70 can be used to establish and maintain potent Th1 immune responses.…”
Section: Discussionmentioning
confidence: 69%
“…So far DC are thought to represent the major source of IL-12p70. However, IL-12p70 production within DC is known to be tightly controlled, usually requiring multiple stimuli to synergize and to induce its expression (30). In fact, we identified monocytes as the major source of IL-12p70 upon ssRNA stimulation within PBMC.…”
Section: Discussionmentioning
confidence: 84%
“…1A). In concert with the role of TLR8 in the production of NF-κB-dependent cytokines (33)(34)(35), IRS957 also caused a significant decrease in secretion of TNF-α, IL-6, and IL-10 by Bb-infected monocytes (Fig. 1B).…”
mentioning
confidence: 97%